The potential role of soluble fibre in the treatment of hypercholesterolaemia. Issue 873 (July 1998) - Coats, A. J.
Abstract : The three major modifiable coronary risk factors are smoking, hypertension, and hypercholesterolaemia. Serum cholesterol levels are above the desirable level of 5.2 mmol/l in 79% of men and 65% of women aged between 35 and 50 years and thus are an important target for intervention. In this paper, the role of nonpharmacological intervention with soluble fibre in treating mild to moderate primary hypercholesterolaemia is reviewed. Evidence from controlled studies shows that soluble fibre can be effective in lowering cholesterol by clinically significant amounts. It is stressed, however, that risk factors for coronary heart disease are interactive and attention is shifting to addressing multiple rather that individual factors.